Land based on-growing of Atlantic cod (Gadus morhua) and salmon (Salmo salar) using Recirculation Aquaculture Systems in the Basque Country: contributions to scientific understanding of economic feasibility, environmental sustainability of economic acceptability - Badiola Amillategui, Maddi (2017)
274 p. Animal farming systems, including fish farming, are regarded to be a major cause of problems such as resource (water and land) depletion and climate change. Their required intensification represents a relevant cause of environmental concern at global level. In aquaculture, the option for reducing the environmental footprint of aquatic animal production and mitigating many of the impacts associated with traditional commercial fish culture technologies (i.e. net pens, ponds, flow-through systems) is Recirculating Aquaculture System (RAS) technology. The present work studies the feasibility of using RAS to rear cold water species such as Atlantic cod (Gadus morhua) and Atlantic salmon (Salmo salar) in the Basque coastal area. The study is made from four different perspectives: technical, economic, environmental and societal. The viability of the technology is tested coupled with the surrounding environment; the cost/benefits of producing fish in the local market are analyzed; the environmental performance and the created impacts are studied; and the final product¿s acceptability is studied among local consumers and seafood experts. Moreover, a new environmental assessment is presented and detailed knowledge of the main issues and future challenges are obtained. AZTI TEKNALIA